Aging and Cohort Changes in Sports and Physical Training from the Golden Decades Onward: A Cohort Study in Switzerland - Lalive d’Epinay, Christian; Maystre, Carole; Bickel, Jean-François (Loisir et Société / Society and Leisure)

(untitled) (Presses de l’Université du Québec, 2001)
AbstractFor most analysts, the Golden Decades (roughly 1950-1980) mark a period of far-reaching change – both structural and cultural – in Western societies. In an attempt to link the macro, societal transformation with individual behavior, the authors elaborate the “context-and-cohort-change” paradigm (as opposed to the “age-related-decline” paradigm), according to which they scrutinize the participation in sports and physical training at two stages (mid-life, third age) of adult life of the members of two cohorts (C1, born 1905-1914, N = 1012; C2, born 1920-1929, N = 661).The results show (a) a robust intercohort increase in the rate of exercisers from C1 to C2; (b) no significant longitudinal decline in participation from mid-life to third age, either in C1 or in C2, but a high rate of turnover among exercisers, with “late exercisers” filling the gaps left by the “dropouts”; (c) changes in the sociodemographic composition of exercisers, reflecting a move away from the pattern in which sports and physical exercise were mostly a male, urban, and upper-class activity, to another, much more generalized and democratic pattern.